«One belt, one road» initiative in Central Asia (The Journal of Psychology and Sociology, 2020)
This article analyses the social perception of the “One Belt, One Way” initiative, the degree of awareness of the Central Asian countries about the implementation of this project, the specifics of per- ception and the role of the media in influencing the perceptions of the “One Belt, One Way” initiative. The article also shows the results of review analysis, indicating that the export of Chinese production power to Kazakhstan as part of the One Belt, One Way Initiative reinforces the anti-Chinese mood in the country, as evidenced by anti-Chinese rallies. The article also notes that these phenomena are wave-like, however, it has a significant impact on the development of the project in certain regions. The article provides a very detailed analysis of the economic, political and social problems of the One Belt, One Way initiative addressed by such authors as Sarah Lane, Marlene Laruelle, Azad Garibov, Paulo Duarte, Safovudin Dzhaborov. Also, analysis of the article by Burkhanov A., Yen Won Chen, addressing the is- sue of perception of China, Chinese and Chinese migration to Kazakhstan. In the works of these authors, the social aspect is addressed, but the political and economic aspects are considered in more depth. It also considers historical and cultural factors and issues of institutional capacity and marginality that may impede China’s initiative.Key words: initiative One belt, one way, China, Central Asia, social perception.